The Paradox of Recognition Principles in Village Law in Ammatoa Kajang Indigenous Community - *, Sampean; Wahyuni, Ekawati Sri; Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The Village Law has stipulated thirteen principles. One of the principles is recognition. The principle of recognition is a turning point in the reformation of the customary law of in Indonesia. The previous studies have founded recognition of the management and use of communal forest. This research focuses on the paradox of recognition of the administration of indigenous government. The implementation of Village Law has replaced the regional autonomy law: from decentralization – residual to recognition – subsidiarity. The inclusion of the principle of recognition – subsidiarity in the village law was implications for changes in the regulation of social order and governance. This research based on constructivism paradigm and qualitative method, with in depth interviews, purposive sampling, observations, and historical archivings. We had analyzed social construction of recognition to indigenous communities in ruling their government. The results indicate that the social construction of recognition in the political aspects of laws and regulations has not been able to meet the needs of indigenous peoples to arrange their government. This study questions regional approach to support the frameworks of desa adat.